The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/ccd.28488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stent diameter on outcomes following percutaneous coronary intervention with second‐generation drug‐eluting stents: Results from a large single‐center registry

Abstract: Background In patients treated with bare metal stents and first‐generation drug‐eluting stents (DES) smaller stent diameter (SD) has been associated with worse long term outcomes after percutaneous coronary intervention (PCI). Data on the impact of small SD on outcomes after PCI with second‐generation DES is scarce. Methods Consecutive patients treated with second‐generation DES between 2010 and 2016 were included in a single tertiary center. Patients were grouped according to SD: ≤2.50 mm, 2.75 ≤ 3.00 mm, 3.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Overall, the 2-year incidence of MACE in this study is 13.3% (15.0% in WMG vs. 11.2% in IMG), which is consistent with the incidence in recent relevant studies [20][21][22][23] . However, this study showed a signi cant difference in mortality between two groups, which has an obvious discrepancy with previous studies about ICWM for patients after PCI 8-10, 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the 2-year incidence of MACE in this study is 13.3% (15.0% in WMG vs. 11.2% in IMG), which is consistent with the incidence in recent relevant studies [20][21][22][23] . However, this study showed a signi cant difference in mortality between two groups, which has an obvious discrepancy with previous studies about ICWM for patients after PCI 8-10, 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, caution should be taken when interpreting the results. Second, although SSA is strongly correlated with reference vessel diameter and SD (11,27). However, no information on reference vessel diameter has been reported thus far.…”
Section: Discussionmentioning
confidence: 89%
“…Although the data on the association between SSA and MACEs after PCI is very limited, the length and diameter of stent have been reported as independent predictors of MACEs after PCI with DES implantation (11,(14)(15)(16)(17). For instance, the results from a meta-analysis found that females with smaller SDstreated with PCI had ahigher risk of definite stent thrombosis and target lesion revascularization, consistent with earlyand newgenerations of DES (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 In this issue, Pitt et al report outcomes of small vessel intervention compared to large vessel revascularization using second generation stent sizing as a surrogate for randomization in a large single center retrospective study. 5 17,607 patients at an expert and busy tertiary care center were stratified into four groups by stent diameters (SD), but not core-lab adjudicated vessel size, based on the smallest target vessel intervened on. Clinical outcomes were then reported 1-year as composite primary end point of death, MI, or TVR which were adjusted for differences in demography, procedural, and co-morbidity characteristics.…”
mentioning
confidence: 99%